2018
DOI: 10.5194/acp-18-11663-2018
|View full text |Cite
|
Sign up to set email alerts
|

Secondary organic aerosol (SOA) yields from NO<sub>3</sub> radical + isoprene based on nighttime aircraft power plant plume transects

Abstract: Abstract. Nighttime reaction of nitrate radicals (NO 3 ) with biogenic volatile organic compounds (BVOC) has been proposed as a potentially important but also highly uncertain source of secondary organic aerosol (SOA). The southeastern United States has both high BVOC and nitrogen oxide (NO x ) emissions, resulting in a large model-predicted NO 3 -BVOC source of SOA. Coal-fired power plants in this region constitute substantial NO x emissions point sources into a nighttime atmosphere characterized by high regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 93 publications
(97 reference statements)
7
49
0
Order By: Relevance
“…While the exact mechanisms responsible for the formation of low volatility organic nitrates still remains to be understood, we found that the overall efficiency of nighttime biogenic SOA formation, as characterized by the ΔOA/ΔCO ratio, was about 100 μg m −3 ppmv, which falls in the range 77-157 μg m −3 ppmv previously estimated for enhanced daytime SOA formation from mixed anthropogenic and biogenic emissions during CARES (Shilling et al, 2013). Using a box model to calculate the amounts of isoprene reacted, we estimated SOA mass yields ranging from 0 to 0.55, which are a factor of 5 to 10 higher than measured in chamber studies (Ng et al, 2008;Rollins et al, 2009) but consistent with the mass yields estimated from field measurements (Fry et al, 2018). Further research is needed to fully elucidate the dominant NO 3 oxidation pathways so they can be represented in atmospheric aerosol models to reliably predict nighttime SOA formation from anthropogenic-biogenic interactions in a larger realm.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…While the exact mechanisms responsible for the formation of low volatility organic nitrates still remains to be understood, we found that the overall efficiency of nighttime biogenic SOA formation, as characterized by the ΔOA/ΔCO ratio, was about 100 μg m −3 ppmv, which falls in the range 77-157 μg m −3 ppmv previously estimated for enhanced daytime SOA formation from mixed anthropogenic and biogenic emissions during CARES (Shilling et al, 2013). Using a box model to calculate the amounts of isoprene reacted, we estimated SOA mass yields ranging from 0 to 0.55, which are a factor of 5 to 10 higher than measured in chamber studies (Ng et al, 2008;Rollins et al, 2009) but consistent with the mass yields estimated from field measurements (Fry et al, 2018). Further research is needed to fully elucidate the dominant NO 3 oxidation pathways so they can be represented in atmospheric aerosol models to reliably predict nighttime SOA formation from anthropogenic-biogenic interactions in a larger realm.…”
Section: Discussionsupporting
confidence: 84%
“…The figure also shows the estimated overall SOA mass yields calculated by dividing the observed SOA masses by the corresponding modeled amounts of total isoprene mass reacted. The overall yields range from 0 to 0.35 and are consistent with those estimated for nighttime isoprene SOA formation from field measurements by Fry et al (2018).…”
Section: Soa Yield Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…For the majority of nitrate-containing aerosol regardless of the class (i.e., inorganic or organic), the nitrate moiety (i.e., -NO2, -ONO2, and -O2NO2) was known to be thermally fragmented into NO + and NO2 + and was measured as NO3 (Farmer et al, 2010). As many past studies have demonstrated the feasibility to separate the contribution of inorganic (NO3,Inorg) and organic nitrate (NO3,Org) to the measured NO3 based on the ratio of NO + and NO2 + (Fry et al, 2009;Farmer et al, 2010;Xu et al, 2015b;Kiendler-Scharr et al, 2016;Fry et al, 2018), we used Eq. (1) presented in Farmer et al (2010) to obtain NO3,Org.…”
Section: Instrumentation and Data Analysismentioning
confidence: 99%
“…Journal of Geophysical Research: Atmospheres indicate that nighttime power plant plumes were widespread horizontally but confined vertically, transporting as fanning plumes (Brown et al, 2012;Fibiger et al, 2018;Fry et al, 2018;Stull, 1988). The profiles also show the SO 2 plumes were situated just above the onset of a steeper gradient in potential temperature that indicates the nocturnal boundary layer.…”
Section: /2018jd030086mentioning
confidence: 99%